Efficient OFDM transceiver design for VLC sys-tems in fading channel - J, Jayakumari; k J, Rakhi (International Journal of Engineering and Technology, 2018)
With the widespread effective usage of LEDs the visible light communication (VLC) system has brought out an increasing interest in the field of wireless communication recently. VLC is envisioned to be an appealing substitute to RF systems because of the advantages of LEDs such as high communication security, rich spectrum, etc. For achieving bearable inter symbol interference (ISI) and high data rates, OFDM can be employed in VLC. In this paper, the performance of VLC system with popular unipolar versions of OFDM viz. Flip-OFDM and ACO-OFDM is analyzed in fading channels. From the simulation results it is seen that the Flip-OFDM-VLC system outperforms the ACO-OFDM-VLC system in terms of bit error rate and is well suited for future 5G applications.
Keywords: 5G; ACO-OFDM; Flip-OFDM; LTE; VLC.